CELL-ENGINEERING DESIGNS TRANSPLANTED INTO LIVER PROVIDE WITH PROLONGED SUPPORT OF RECOVERY PROCESSES IN DAMAGED LIVER - M. Y. Shagidulin; N. A. Onischenko; M. E. Krasheninnikov; I. M. Iljinsky; A. V. Lyundup; V. I. Sevastyanov; N. P. Mogeiko; S. V. Gautier (Вестник трансплантологии и искусственных органов, 2013)
Aim is to develop a method for a prolonged support of recovery processes in damaged liver. Materials and me- thods. It was carried out 3 groups of experiments on Wistar rats with the modeling of chronic fibrotic liver injury (n = 70): I group control (n = 20); in the II group (n = 20) a suspension of liver cells was transplanted into liver; in the III group (n = 30) cell-engineering designs (CED), which contained liver cells and BM MMSC, enclosed in a heterogeneous biodegradable gel “Sphero®GEL-long” were transplanted into damaged liver. The activity of recovery processes was evaluated by using biochemical and morphological methods in dynamics on 30, 60, 90 and 180 days. Results. It was shown that in the II and III gr. significantly accelerated the recovery processes in damaged livers compared with the I gr. The normalization of biochemical parameters took place in II and III du- ring 30 days instead of 90 days in the I group. However, the normalization of morphological signs of hepatocytes theirs viability and a degree of defibrotic changes in liver were more pronounced and prolonged in the III group. A study showed integration of CED by liver structures with formation of new bile ducts after 90 and 180 days. Conclusion. Higher levels and prolonged periods of recovery processes in damaged liver after CED transplanta- tion were due to the creation of biologically appropriate conditions for prolonged cell activity, included in their structure (donor liver cells and BM MMSC).